2019
DOI: 10.1128/aac.01473-19
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the α-Methoxy Group on the Reaction of Temocillin with Pseudomonas aeruginosa PBP3 and CTX-M-14 β-Lactamase

Abstract: The prevalence of multidrug-resistant Pseudomonas aeruginosa has led to the reexamination of older “forgotten” drugs, such as temocillin, for their ability to combat resistant microbes. Temocillin is the 6-α-methoxy analogue of ticarcillin, a carboxypenicillin with well-characterized antipseudomonal properties. The α-methoxy modification confers resistance to serine β-lactamases, yet temocillin is ineffective against P. aeruginosa growth. The origins of temocillin’s inferior antibacterial properties against P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The structure of this protein has been well studied by several investigators because of its importance in betalactam resistance in this common human pathogen(12)(13)(14)16). The variant amino acids at positions 342, 599, 600, and 601 mapped to regions known to influence structure-function relationships(20,21). This determination of influence was derived from overlaying PBP2X from S. pneumoniae with the clinically relevant and structurally similar P. aeruginosa PBP3 (PDB: 6UN3) and S. aureus PBP2a (PDB: 1VQQ, chain A).…”
mentioning
confidence: 99%
“…The structure of this protein has been well studied by several investigators because of its importance in betalactam resistance in this common human pathogen(12)(13)(14)16). The variant amino acids at positions 342, 599, 600, and 601 mapped to regions known to influence structure-function relationships(20,21). This determination of influence was derived from overlaying PBP2X from S. pneumoniae with the clinically relevant and structurally similar P. aeruginosa PBP3 (PDB: 6UN3) and S. aureus PBP2a (PDB: 1VQQ, chain A).…”
mentioning
confidence: 99%
“…Examination of the reported PaPBP3 structures ,, reveals the β5-α11 loop (residues 528–539, Figure S10) adopts different conformations. The β-lactam-containing PaPBP3 inhibitors (e.g., amoxicillin, aztreonam, ceftazidime, and piperacillin , ) induce formation of a “hydrophobic wall” composed of Tyr533, Phe532, and residues within the β5-α11 loop together with Tyr503 .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition plots with meropenem and ceftazidime were done to ensure the correct parameters for BOCILLIN FL binding were used. Progress curves were analyzed with KinTek, USA, as described; , reported errors represent the standard error. The acylation of a PBP by BOCILLIN FL (Figure S1) can be described by a simple one-step model .…”
Section: Methodsmentioning
confidence: 99%
“…For many bacteria, the value of each PBP for drug discovery is only starting to be unraveled. For example, some studies have identified PBP3 as an essential transpeptidase for P. aeruginosa growth and therefore a key β-lactam target (Figure 4) [171][172][173], while PBP2 may also represent a good therapeutic target for novel antibiotic discovery [128]. Other researchers used Bacillus subtilis cells to visualize and study PBP inhibition profiles of β-lactam antibiotics in live cells, which allowed the determination of PBPs essential for the growth of the microorganism and their roles in antibiotic resistance [174].…”
Section: Understanding the Transpeptidase Targetsmentioning
confidence: 99%